Review of ‘Domination and the Arts of Resistance’ by James C. Scott - Abdelaali Khalifa; Mohamed Khales (International Journal of Scientific Research and Innovative Studies, 2025)
In his book "Domination and the Arts of Resistance," James C. Scott sought to construct a theoretical framework for understanding how the weak people resist various forms of domination, subordination, and subjugation directed against them. His ideas primarily focused on examining and analyzing the hidden and implicit dimensions of resistance in the discourses and behaviors of subordinate groups, relying on ethnographic data drawn from specific communities in Southeast Asia. Key words : the weak people, domination, public transcript, hidden transcript, infra-politics. Received Date: July 20, 2025 Accepted Date: August 12, 2025 Published Date: August 30, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/423